THE IMPACT OF VISUAL MERCHANDISING MODIFICATIONS IN RELATION TO CUSTOMER SATISFACTION IN A SCHOOL CAFETERIA IN THE CITY OF ARARAQUARA - Cangussu, Caique Araujo; Garcia, Gabriel Gentile; Carrino, Adauto Luiz (Revista Interface Tecnológica, 2020)
In the current context, companies do their best efforts and use many strategies to reach their target audience and satisfy their customers. Merchandising, whose main objectives are to motivate and influence consumer decisions through greater visibility of the product and the brand, appears as an efficient tool for organizations in the search for the desired success. This study aimed to analyze the impact of changes in the visual merchandising of a school cafeteria located in the city of Araraquara - SP, in relation to the satisfaction and view of consumers about the company. As for the methodological procedures, it corresponds to an exploratory and descriptive research, being quantitative and developed through a field study. With regard to data collection, a satisfaction survey was first developed through a structured questionnaire and applied on the spot to the company’s customers before and shortly after the implementation of the changes in relation to visual merchandising, covering a sample of 76 participants. Among the results obtained, it can be concluded that, even though variables such as product prices or production and service methods remain unchanged, the changes made in visual merchandising and exposure, as well as the best configuration of the sales environment with adequate lighting and decoration, generated a significant improvement in customer satisfaction levels.